2000
DOI: 10.1111/j.1095-8649.2000.tb00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme analyses of the genus Trisopterus: taxonomic status and population structure of the poor cod

Abstract: Genetic analysis of the four Trisopterus (Gadidae) taxa suggests that the interrelationships of the two morphs of poor cod (T. minutus minutus in the Atlantic and T. minutus capelanus in the Mediterranean) should be reconsidered. The Mediterranean poor cod T. m. capelanus is more closely related to bib T. luscus than to the Atlantic poor cod, so the population structure in the Atlantic and Mediterranean poor cod must be considered separately. Among 635 Atlantic individuals there was some evidence of poor cod p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
1
15
1
Order By: Relevance
“…Genetic data support this close relationship very well: both the complete mitochondrial DNA of cytochrome b and the nuclear DNA of the rhodopsin genes point to a much closer relationship of T. luscus and T. capelanus than any other combination of two of the four trisopterine species [21,22]. This is a strong confirmation of earlier research in which was found that both species shared the highest number of loci with the same alleles extracted from muscle and liver tissue [18].…”
Section: Trisopterus Capelanus Is a Separate Speciessupporting
confidence: 83%
See 4 more Smart Citations
“…Genetic data support this close relationship very well: both the complete mitochondrial DNA of cytochrome b and the nuclear DNA of the rhodopsin genes point to a much closer relationship of T. luscus and T. capelanus than any other combination of two of the four trisopterine species [21,22]. This is a strong confirmation of earlier research in which was found that both species shared the highest number of loci with the same alleles extracted from muscle and liver tissue [18].…”
Section: Trisopterus Capelanus Is a Separate Speciessupporting
confidence: 83%
“…Closer relationships between A. minutus and N. esmarkii, compared with the other trisopterines, are demonstrated by otolith characteristics and genetics. The greater taxonomic distance of A. minutus and N. esmarkii to T. luscus and T. capelanus is based upon various characteristics of the fishes, such as otolith morphology and genetic data [18,22], and also upon phylogenetic data inferable from fossil otoliths. These data together do not allow including A. minutus in the genus Trisopterus or Neocolliolus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations